Empirical Study Of Mentoring Effectiveness In Petrochemical Plant - Shanmugam, Divakaran (2006)
People are company's asset and they are the vital resource in any organization. The research covered the review of the mentoring programme itself, the mentoring climate in the company, its infrastructure and mentoring process. It attempts to determine whether the mentoring programme has been an effective strategy in the process of staff development , with special reference to the mentorees.